Performance of new gellan gum hydrogels combined with human articular chondrocytes for cartilage regeneration when subcutaneously implanted in nude mice - Oliveira, J. T. (2009)
Gellan gum is a polysaccharide that has been recently proposed by our group for cartilage tissueengineering applications. It is commonly used in the food and pharmaceutical industry and has the ability to form stable gels without the use of harsh reagents. Gellan gum can function as a minimally invasive injectable system, gelling inside the body in situ under physiological conditions and efficiently adapting to the defect site. In this work, gellan gum hydrogels were combined with human articular chondrocytes (hACs) and were subcutaneously implanted in nude mice for 4 weeks. The implants were collected for histological (haematoxylin and eosin and Alcian blue staining), biochemical [dimethylmethylene blue (GAG) assay], molecular (real-time PCR analyses for collagen types I, II and X, aggrecan) and immunological analyses (immunolocalization of collagen types I and II). The results showed a homogeneous cell distribution and the typical round-shaped morphology of the chondrocytes within the matrix upon implantation. Proteoglycans synthesis was detected by Alcian blue staining and a statistically significant increase of proteoglycans content was measured with the GAG assay quantified from 1 to 4 weeks of implantation. Real-time PCR analyses showed a statistically significant upregulation of collagen type II and aggrecan levels in the same periods. The immunological assays suggest deposition of collagen type II along with some collagen type I. The overall data shows that gellan gum hydrogels adequately support the growth and ECM deposition of human articular chondrocytes when implanted subcutaneously in nude mice.